Գեւորգ Երզնկացու «Վասն տէրունական լրմանց կանխելոյ եւ անագանելոյ Զատկի» աշխատութիւնը - Էյնաթեան, Ջուլիետտա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Празднование Воскресения Христова (Пасхи) совершается в воскресенье, следующее за первым днем полнолуния после весеннего равноденствия. Геворг Ерзнкаци подробно описывает 354-дневное движение Луны и 365-дневное движение Земли, а также то, как это приводит к раннему или позднему празднованию Пасхи. Эта работа Геворга Ерзнкаци публикуется впервые, из рукописи Матенадарана N 2001. The celebration of the feast of Christ’s Resurrection (Easter) takes place on the Sunday following the first day of the full moon after the vernal equinox - March 21st. Gevorg of Yerznka describes in detail the 354-day motion of the Moon and the 365-day motion of the Earth, and how this leads to an early or late celebration of Easter. This work by Gevorg of Yerznka is published for the first time, based on manuscript N 2001 of Mesrop Mashtots manuscript library.
Keywords: Հաղորդումներ; Ձեռագիր մատյան